A kind of all-solid-state supercapacitor based on flexible fiber electrode and preparation method thereof

By using a combination of high-specific capacitance flexible fiber electrode and activated carbon negative electrode in the fibrous flexible supercapacitor, the problems of low specific capacity and narrow voltage window of the fibrous supercapacitor are solved, and flexible energy storage devices with high performance and long life are achieved. Suitable for flexible wearable devices.

CN118398398BInactive Publication Date: 2024-12-17HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410682772.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing fibrous flexible supercapacitors have problems such as low specific capacity, narrow voltage window, complex preparation process and poor adhesion between positive and negative electrodes and electrolytes, which limits their application in the field of flexible wearables.

Method used

Using an all-solid fibrous asymmetric supercapacitor based on a high specific capacitance flexible fiber electrode, the composite electrode of Co-MOF nanosheets and nickel hydroxide coated cobalt-manganese oxide nanosheets were deposited layer by layer on the nickel wire, and combined with activated carbon The negative electrode combines to form a wide operating voltage window and a high energy density device.

Benefits of technology

It realizes flexible supercapacitors with high voltage, high energy density, high power density and long cycle life, and has almost no attenuation of electrochemical performance in folding and bending states, meeting the needs of flexible wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118398398B_ABST
    Figure CN118398398B_ABST
Patent Text Reader

Abstract

The present invention relates to an all-solid-state supercapacitor based on a flexible fiber electrode and a preparation method thereof. First, a Co-MOF precursor (NW@Co-MOF) on a current collector nickel wire is obtained by a liquid phase method, and then the NW@Co-MOF is placed in a manganese salt solution for static reaction to obtain a cobalt manganese oxide electrode (NW@(Co,Mn)(Co,Mn)2O4) derived from the Co-MOF precursor as a sacrificial template, and then an electrochemical deposition method is used to obtain a cobalt manganese oxide nanosheet composite electrode (NW@(Co,Mn)(Co,Mn)2O4@Ni(OH)2) coated with nickel hydroxide having a heterogeneous structure, and finally a gel electrolyte is used to assemble the composite electrode and a fibrous activated carbon negative electrode into an all-solid-state supercapacitor. The flexible fiber electrode has excellent specific capacity and rate performance due to the synergistic effect of multiple components. The assembled all-solid-state supercapacitor has a wide voltage window, a high energy density and a long cycle performance, which can better meet the needs of practical applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of flexible energy storage technology, and specifically relates to an all-solid-state fiber-shaped supercapacitor based on flexible fiber electrodes and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of wearable devices and portable electronic devices, the demand for high-performance flexible energy storage devices has become more urgent. Flexible supercapacitors have attracted widespread attention due to their advantages such as light weight, foldability, bendability, fast charge and discharge, long cycle life, and high power density. Among them, fiber-shaped flexible supercapacitors have the advantages of small size and good flexibility compared to planar or three-dimensional flexible supercapacitors, making them a highly-regarded flexible energy storage device.

[0003] However, current fiber-shaped flexible supercapacitors have problems such as low specific capacity, narrow voltage window, complex preparation process, and poor adhesion between positive and negative electrodes and electrolytes, which limit their application in the field of flexible wearables. Improving the specific capacity of electrodes and assembling asymmetric supercapacitors can effectively improve the voltage window and energy density of devices, while developing simple and large-scale preparation methods will help further promote the market application of flexible fiber-shaped supercapacitors. Therefore, we proposed a high-performance all-solid-state fiber-shaped asymmetric supercapacitor based on high-specific capacity flexible fiber electrodes and its preparation method. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention proposes an all-solid-state supercapacitor based on a flexible fiber electrode and a preparation method thereof. The flexible fiber electrode of the present invention has the advantages of high specific surface area, high conductivity, and rich active sites. The all-solid-state fiber-shaped supercapacitor has the advantages of high voltage, high energy density, high power density, and long cycle life, and has excellent flexibility, which can better meet the development requirements of new wearable devices.

[0005] A first aspect of the present invention provides a method for preparing a flexible fiber electrode, comprising the following steps:

[0006] S1. Dissolve cobalt salt and dimethylimidazole in deionized water respectively and stir evenly, then quickly mix and stir the two solutions to obtain a precursor solution;

[0007] S2, placing the pretreated nickel wire in the above-mentioned precursor solution and standing for a period of time, washing and drying, and obtaining a Co-MOF precursor (NW@Co-MOF) in situ grown on the current collector nickel wire;

[0008] S3, placing the NW@Co-MOF in a manganese salt solution and letting it stand for a period of time, then washing and drying to obtain a cobalt manganese oxide electrode (NW@(Co,Mn)(Co,Mn)2O4) derived from the Co-MOF precursor as a sacrificial template;

[0009] S4. Using the above-mentioned NW@(Co,Mn)(Co,Mn)2O4 as the working electrode, the platinum sheet as the counter electrode, and the saturated calomel electrode as the reference electrode, in a deposition solution containing nickel salt, a cobalt manganese oxide nanosheet composite electrode (NW@(Co,Mn)(Co,Mn)2O4@Ni(OH)2) coated with nickel hydroxide having a heterogeneous structure is obtained by electrochemical deposition under a three-electrode system.

[0010] The preferred method of the above preparation method is as follows:

[0011] The cobalt salt in S1 is any one of cobalt nitrate, cobalt sulfate, cobalt acetate and cobalt chloride; the cobalt ion concentration in the cobalt salt solution is 4-40 mg / mL; and the mass concentration of the dimethylimidazole solution is 20-60 mg / mL.

[0012] The pretreatment operation in S2 is specifically: placing the nickel wire in a ferric chloride solution for corrosion, wherein the molar concentration of the ferric chloride solution is 0.1 to 10 M, and the corrosion time is 2 to 20 minutes.

[0013] The standing time in S2 is 2 to 10 hours, the drying temperature is 50 to 100° C., and the drying time is 6 to 24 hours.

[0014] The manganese salt in S3 is any one of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride; the manganese ion concentration in the manganese salt solution is 0.001-1 mol / L.

[0015] The standing time in S3 is 0.5 to 20 hours, the drying temperature is 25 to 80° C., and the drying time is 6 to 48 hours.

[0016] The nickel salt in S4 is any one of nickel sulfate, nickel nitrate, nickel acetate and nickel chloride; the nickel ion concentration in the nickel salt solution is 0.01-1 mol / L.

[0017] The electrochemical deposition in S4 is constant potential deposition, the voltage range is -1.5 to -0.1 V, and the deposition time is 20 to 2000 s.

[0018] The second aspect of the present invention provides a flexible fiber electrode prepared by the method described in the first aspect, wherein the fiber electrode is a cobalt manganese oxide nanosheet composite electrode coated with nickel hydroxide having a heterogeneous structure (NW@(Co,Mn)(Co,Mn)2O4@Ni(OH)2).

[0019] A third aspect of the present invention provides a method for preparing an all-solid-state supercapacitor, comprising the following steps:

[0020] Step 1: Mixing activated carbon, conductive carbon black and a binder into an N-methyl-2-pyrrolidine solution to form a uniform mixed slurry, and then uniformly coating the mixed slurry on a nickel wire and drying it to obtain a fibrous activated carbon negative electrode;

[0021] Step 2: Stirring PVA vigorously at high temperature to completely dissolve it in deionized water to obtain a clear and transparent PVA solution, then cooling the PVA solution and adding KOH electrolyte solution dropwise under vigorous stirring to obtain a PVA-KOH gel electrolyte;

[0022] Step three, immerse the NW@(Co,Mn)(Co,Mn)2O4@Ni(OH)2 composite electrode described in the second aspect of the present invention and the fibrous activated carbon negative electrode described in step one into the PVA-KOH gel electrolyte described in step two, wrap the two electrodes together, and leave them overnight until the gel electrolyte solidifies to obtain an all-solid-state fibrous flexible asymmetric supercapacitor.

[0023] Preferably, in step one, the mass ratio of activated carbon, conductive carbon black and binder is 7:2:1.

[0024] The fourth aspect of the present invention provides an all-solid-state fiber-shaped supercapacitor prepared by the method described in the third aspect.

[0025] The beneficial effects of the present invention are as follows:

[0026] 1. The fiber-shaped electrode directly deposits the conductive material and active material layer by layer on the nickel wire, avoiding the use of binders in the traditional electrode preparation process, effectively improving the mechanical properties of the flexible electrode, and solving the problem of active material shedding during the folding and bending of the traditional coated electrode. At the same time, it also avoids the slurry preparation and coating process in the traditional electrode preparation process, greatly saving the electrode preparation cost.

[0027] 2. The fiber-shaped electrode has excellent specific capacity and rate performance due to the synergistic effect of multiple components. Among them, Co-MOF nanosheets as precursors provide a large specific surface area, and the addition of Mn 2+ The formed (Co, Mn)(Co, Mn)2O4 nanosheets not only inherit the large specific surface area of ​​the precursor, but also have high conductivity, which accelerates the electron transfer rate. Ni(OH)2 with high theoretical specific capacitance is plated on the surface of (Co, Mn)(Co, Mn)2O4 nanosheets with large specific surface area and high conductivity. The synergistic effect between the two components makes the electrode performance produce a "1+1>2" effect.

[0028] 3. By adjusting the solution type, concentration, electrodeposition voltage, and electrodeposition time, the phase, morphology, and deposition amount of the active material can be flexibly controlled.

[0029] 4. The fiber-shaped electrode can be matched with a flexible negative electrode material to obtain a flexible energy storage device with a wide operating voltage window. The obtained fiber-shaped asymmetric supercapacitor has a wide voltage window, high energy density and long cycle performance, which can better meet the needs of practical applications. Moreover, the fiber-shaped asymmetric supercapacitor has good flexibility, and the electrochemical performance is almost unattenuated in the folded and bent state, which can well meet the application needs of the flexible wearable field. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the NW@CMO@Ni(OH)2 composite electrode of Example 1 of the present invention;

[0031] Figure 2 This is an SEM magnified image of the NW@CMO@Ni(OH)2 composite electrode of Example 1 of the present invention;

[0032] Figure 3 TEM image of the NW@CMO@Ni(OH)2 composite electrode of Example 1 of the present invention;

[0033] Figure 4 This is the XRD spectrum of the NW@CMO@Ni(OH)2 composite electrode of Example 1 of the present invention;

[0034] Figure 5 This is the XPS spectrum of the NW@CMO@Ni(OH)2 composite electrode of Example 1 of the present invention;

[0035] Figure 6 CV curves of NW@CMO@Ni(OH)2 of Example 1 of the present invention and comparative examples NW@CMO, NW@Ni(OH)2, and NW@Co-MOF@Ni(OH)2;

[0036] Figure 7 The area specific capacity of NW@CMO@Ni(OH)2 of Example 1 of the present invention and the comparative examples NW@CMO, NW@Ni(OH)2, and NW@Co-MOF@Ni(OH)2 at different current densities;

[0037] Figure 8 The cyclic voltammetry curves of the positive and negative electrodes of the fiber-shaped asymmetric supercapacitor of Example 2 of the present invention;

[0038] Fig. 9 1 is the charge and discharge curve of the fiber-shaped asymmetric supercapacitor of Example 2 of the present invention at different current densities;

[0039] Fig.10 The energy density-power density diagram of the fiber-shaped asymmetric supercapacitor of Example 2 of the present invention and its performance comparison with the reported fiber-shaped capacitors;

[0040] Fig.11 Cyclic voltammetry curves of the fiber-shaped asymmetric supercapacitor of Example 2 of the present invention at different bending angles;

[0041] Fig.12 This is a digital photo of the fibrous asymmetric supercapacitor according to Example 2 of the present invention woven into a glove. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] A method for preparing a flexible fiber electrode comprises the following steps:

[0045] S1: 2.32 g of cobalt nitrate hexahydrate was added to 160 mL of deionized water and stirred evenly, 5.248 g of dimethylimidazole was added to 160 mL of deionized water and stirred evenly, and then the two solutions were quickly mixed and magnetically stirred for 30 min to obtain a precursor solution;

[0046] S2: The pretreated nickel wire (0.7 M ferric chloride solution, corrosion for 10 min) was placed in the above precursor solution for 8 h, then rinsed with deionized water and ethanol alternately, and dried at 60 °C for 12 h to obtain the Co-MOF precursor (NW@Co-MOF) in situ grown on the current collector nickel wire;

[0047] S3: The above-mentioned NW@Co-MOF was placed in an aqueous solution of manganese sulfate (0.34 g of manganese sulfate monohydrate dissolved in 200 mL of deionized water, 0.01 mol / L) and allowed to stand for 8 h, then rinsed alternately with ethanol and deionized water, and dried at 60°C for 24 h to obtain a cobalt manganese oxide electrode (NW@(Co,Mn)(Co,Mn)2O4) derived from the Co-MOF precursor as a sacrificial template.

[0048] S4: Using the above-mentioned NW@(Co,Mn)(Co,Mn)2O4 (1.5cm) as the working electrode, platinum sheet as the counter electrode, saturated calomel electrode as the reference electrode, and 50mM nickel nitrate hexahydrate solution as the deposition solution, a one-step constant potential deposition method was used under a three-electrode system to rapidly deposit for 200s at -1.1V to obtain a nickel hydroxide-coated cobalt manganese oxide nanosheet composite electrode (NW@(Co,Mn)(Co,Mn)2O4@Ni(OH)2, abbreviated as NW@CMO@Ni(OH)2) with a heterogeneous structure.

[0049] Example 2

[0050] A method for preparing an all-solid-state fiber-shaped supercapacitor comprises the following steps:

[0051] Step 1: Mix activated carbon, conductive carbon black and binder in N-methyl-2-pyrrolidine solution in a ratio of 7:2:1 to form a uniform mixed slurry, and then evenly coat the mixed slurry on the nickel wire and dry it to obtain a fibrous activated carbon negative electrode.

[0052] Step 2: 6 g of PVA was completely dissolved in 40 mL of deionized water at 90 °C under vigorous stirring for 30 minutes to obtain a clear and transparent PVA solution. Subsequently, when the temperature dropped to 60 °C, 10 mL of 1 M KOH solution was added dropwise to the PVA solution under vigorous stirring to obtain a PVA-KOH gel electrolyte.

[0053] Step 3: Immerse the NW@CMO@Ni(OH)2 composite electrode described in Example 1 and the fibrous activated carbon negative electrode described in Step 1 in the PVA-KOH gel electrolyte for 10 minutes, wrap the two electrodes together, and leave them overnight until the gel electrolyte solidifies to obtain an all-solid-state fibrous flexible asymmetric supercapacitor.

[0054] Comparative Example 1

[0055] This example provides a method for preparing a flexible fiber electrode, using the same liquid phase method to obtain a cobalt manganese oxide electrode (NW@(Co,Mn)(Co,Mn)2O4, abbreviated as NW@CMO) derived from a Co-MOF precursor as a sacrificial template.

[0056] Comparative Example 2

[0057] This example provides a method for preparing a flexible fiber electrode, using the same electrodeposition process to directly deposit nickel hydroxide on a nickel wire to obtain an electrode coated with nickel hydroxide (NW@Ni(OH)2).

[0058] Comparative Example 3

[0059] This example provides a method for preparing a flexible fiber electrode, in which a nickel hydroxide-coated Co-MOF nanosheet composite electrode (NW@Co-MOF@Ni(OH)2) is obtained by depositing the same electrodeposition process on a nickel wire.

[0060] Depend on Figure 1-3 It can be seen that (Co, Mn)(Co, Mn)2O4@Ni(OH)2 is densely deposited on the surface of the nickel wire. Figure 4 It can be seen that (Co, Mn)(Co, Mn)2O4 and Ni(OH)2 phases were successfully formed. Figure 5 The presence of Ni, Co, and Mn elements in the electrode can be seen.

[0061] Depend on Figure 6 , 7 It can be seen that the NW@(Co,Mn)(Co,Mn)2O4@Ni(OH)2 composite electrode has obvious electrochemical performance advantages. First, the Co-MOF precursor is synthesized in situ on the metal fiber nickel wire, which has a large specific surface area and avoids the "dead volume" caused by the binder. 2+ The (Co, Mn)(Co, Mn)2O4 nanosheets were formed, which adjusted the electronic structure of the precursor and improved the conductivity, thus stimulating the electrochemical activity and creating conditions for the uniform deposition of Ni(OH)2. Finally, the high-capacitance Ni(OH)2 was plated by electrodeposition, achieving a fast and reversible Faradaic reaction.

[0062] like Figure 8 These are the different working voltage ranges of the two fiber electrodes. Fig. 9 The charge and discharge curves of the assembled all-solid-state asymmetric supercapacitor at different current densities show that the operating voltage range of the device has been widened to 1.5V and it has a higher specific capacity. Fig.10 This is the energy density-power density relationship diagram of the all-solid-state asymmetric supercapacitor. It can be seen that the device has higher energy density and power density, and its performance is better than the reported fiber-shaped supercapacitors. Fig.11 The cyclic voltammetry curves of the device at different bending angles show that the electrochemical performance of the all-solid-state asymmetric supercapacitor remains almost unchanged under different deformation states. Fig.12 Digital photograph of an asymmetric supercapacitor woven into a glove, demonstrating its potential for use in flexible wearables.

[0063] The fibrous asymmetric supercapacitor and the preparation method thereof provided in the above-mentioned embodiments of the present invention focus on preparing a fibrous electrode with high specific capacity, high conductivity and excellent mechanical properties, so as to improve the problems of insufficient electrochemical performance of existing flexible fibrous electrodes and attenuation or even failure of electrochemical performance during deformation.

[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a flexible fiber electrode, characterized in that: The following steps are involved: S1. Dissolve cobalt salt and dimethylimidazole in deionized water respectively and stir evenly, then quickly mix and stir the two solutions to obtain a precursor solution; S2, placing the pretreated nickel wire in the above-mentioned precursor solution and standing for a period of time, washing and drying, and obtaining the Co-MOF precursor NW@Co-MOF in situ grown on the current collector nickel wire; S3, placing the NW@Co-MOF in a manganese salt solution and letting it stand for a period of time, then washing and drying, to obtain a cobalt manganese oxide electrode NW@(Co, Mn)(Co, Mn)2O4 derived from the Co-MOF precursor as a sacrificial template; S4, using the above NW@(Co,Mn)(Co,Mn)2O4 as a working electrode, a platinum sheet as a counter electrode, and a saturated calomel electrode as a reference electrode, in a deposition solution containing nickel salt, a cobalt manganese oxide nanosheet composite electrode NW@(Co,Mn)(Co,Mn)2O4@Ni(OH)2 with a heterogeneous structure is obtained by electrochemical deposition under a three-electrode system; Wherein, the manganese salt in step S3 is manganese sulfate, and the manganese ion concentration in the manganese salt solution is 0.01 mol / L; Wherein, the electrochemical deposition in step S4 is constant potential deposition, the voltage is -1.1V, and the deposition time is 200 s; The cobalt salt in step S1 is any one of cobalt nitrate, cobalt sulfate, cobalt acetate, and cobalt chloride; the cobalt ion concentration in the cobalt salt solution is 4 to 40 mg / mL; the mass concentration of the dimethylimidazole solution is 20 to 60 mg / mL; In step S3, the standing time is 0.5 to 20 h, the drying temperature is 25 to 80° C., and the drying time is 6 to 48 h; The nickel salt in step S4 is any one of nickel sulfate, nickel nitrate, nickel acetate and nickel chloride; the nickel ion concentration in the nickel salt deposition solution is 0.01-1 mol / L.

2. The method for preparing a flexible fiber electrode according to claim 1, characterized in that: The pretreatment operation in step S2 is specifically: corroding the nickel wire in a ferric chloride solution, wherein the molar concentration of the ferric chloride solution is 0.1 to 10 M and the corrosion time is 2 to 20 min.

3. A flexible fiber electrode, characterized in that: The method is prepared by any one of claims 1 to 2.

4. A method for preparing an all-solid-state supercapacitor, characterized in that: The following steps are involved: Step 1: Mixing activated carbon, conductive carbon black and a binder into an N-methyl-2-pyrrolidine solution to form a uniform mixed slurry, and then uniformly coating the mixed slurry on a nickel wire and drying it to obtain a fibrous activated carbon negative electrode; Step 2: Stirring PVA vigorously at 90° C. to completely dissolve it in deionized water to obtain a clear and transparent PVA solution, then cooling the PVA solution and adding KOH electrolyte solution dropwise under vigorous stirring to obtain a PVA-KOH gel electrolyte; Step 3: immerse the flexible fiber electrode as described in claim 3 and the fibrous activated carbon negative electrode as described in step 1 into the PVA-KOH gel electrolyte as described in step 2, wrap the two electrodes together, and leave them overnight until the gel electrolyte solidifies to obtain an all-solid-state fibrous flexible asymmetric supercapacitor.

5. An all-solid-state supercapacitor, characterized in that: The method according to claim 4 is used to prepare the product.